2006
DOI: 10.1080/13803610600808115
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of national test performance: A two-level approach

Abstract: The research project presented in this article was set in the Swedish school context and carried out on a set of compulsory national tests for English, Swedish, and mathematics used at the end of compulsory school. The aims were: (a) to gain a deeper knowledge of the internal structure of the tests and (b) to separate individual performance from school performance. Individual test results from a representative sample of approximately 30% of the cohort (n ¼ 26,360) constituted the data. Factor analysis, of a ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
3
4
0
Order By: Relevance
“…Stated differently, differences between schools tended to be smaller for linguistic tasks with a selected response format than for receptive tasks requiring constructed responses. This is in line with observations reported by Åberg-Bengtsson and Erickson (2006) and will be further discussed below.…”
Section: Distribution Of Variances Between Student and School Levelssupporting
confidence: 92%
See 2 more Smart Citations
“…Stated differently, differences between schools tended to be smaller for linguistic tasks with a selected response format than for receptive tasks requiring constructed responses. This is in line with observations reported by Åberg-Bengtsson and Erickson (2006) and will be further discussed below.…”
Section: Distribution Of Variances Between Student and School Levelssupporting
confidence: 92%
“…Similar results have been found in analyses of test performance at student and school levels within the same country, also comprising different subjects/constructs (Åberg-Bengtsson & Erickson, 2006). Åberg-Bengtsson and Erickson (2006) investigated the Swedish national tests for English, Swedish, and mathematics administered at the end of compulsory education and identified a number of factors and dimensions.…”
Section: Dimensionality Of Achievement Testssupporting
confidence: 56%
See 1 more Smart Citation
“…In our model, mathematics and science were related to one joint factor (MathSc 0 ) and the spatial/practical factor was replaced by a narrow aesthetic factor. Furthermore, mathematics has a rather substantial and statistically significant loading on the language factor, a phenomenon observed by Andersson (1998), and also Å berg- Bengtsson and Erickson (2004), who investigated performance on National Tests for grade 9. As shown in Figure 2, both the factorial structure and the pattern of factor loadings make sense with respect to each factor.…”
Section: A Model For Grades From the Leaving Certificatementioning
confidence: 99%
“…The National Agency of Education (2007a) has conducted several studies which have found that the national tests are valuable instruments in achieving equivalence in grades. Studies have also shown that the national tests are reasonably valid as instruments for measuring students' subject knowledge (Å berg-Bengtsson & Erickson, 2006;National Agency for Education, 2007a).…”
Section: The National Testsmentioning
confidence: 97%